A true alternative?: A discourse analysis of the Alternative Spring Break’s online marketing material - Lapalme, Élise (Université d'Ottawa | University of Ottawa, 2017)
Volunteer tourism, otherwise known as voluntourism, is generally defined as a way in which young, unskilled, individuals from the Global North can spend 1 to 4 weeks abroad, contributing to community development or environmental sustainability. Voluntourism is a growing phenomenon and many universities are responding to student demands, while also capitalizing on the key demographic to whom voluntourism is marketed (young students). The Alternative Spring Break (ASB) is one such program that provides students an opportunity to volunteer abroad or in Canada for 1 to 4 weeks. This paper examines the ASB websites of Carleton University, Ryerson University and the University of Western Ontario and uncovers, through a discourse analysis, several challenges with the language of an “alternative experience.” This paper suggests that ASB markets their programs in such a way that students believe they will make a difference abroad, while simultaneously experiencing something alternative to everyday life. Although marketed as such, ASB in fact perpetuates two often cited thematic frames found within the voluntourism literature: neocolonialism and neoliberalism. Through this analysis, this study suggests that the way in which ASB trips are marketed does not fully inform students of the effects of their choice to travel abroad, and thus students perpetuate the idea that they are superior and have come to “help” the “Other.” Key Word: Alternative Spring Break, Voluntourism, Alternative, Neocolonialism, Neoliberalism